Agrifood processing in Africa: Status, challenges, and opportunities - Ellis, Mia; Fang, Jared; McMillan, Margaret S. (AKADEMIYA2063, 2022)
Ashift from agriculture to manufacturing was one of the hallmarks of job creation, poverty reduction, and rapid growth in low-income countries during the latter half of the 20th century. This experience in earlier decades of structural transformation was characterized by labor-absorbing, productivity-increasing manufacturing. Recent structural change in African countries has been markedly different—productivity gains are realized through reallocation of economic activity away from agriculture without the accompanying within-sector productivity growth in nonagriculture, and manufacturing in particular (Diao, McMillan, and Rodrik 2019; Diao et al., 2021; McMillan and Zeufack 2022). This chapter examines the extent to which agrifood processing follows these trends.